Implemetation Of The Make A Suitable Model To Improve The Results Of Learning - St Jauhar; Muliadi Muliadi; Andi Dewi Riang Tati; Bahri Bahri Bahri (Pinisi Journal of Social Science, 2023)
Implemetation of the Make A Suitable Model to Improve the Results of Learning. The problem that lies behind this research is the low learning outcomes of students in social studies subject class in Makassar City. This study aims to describe the application of the make a match type of cooperative learning model to improve social studies learning outcomes in Makassar City. The focus of this researchis the application of the make a match type of cooperative learning model and student learning outcomes. The reasearch approach used in this study is a qualitative approach and the type of research used is Classroom Action Reasearch (CAR) which was carried out in two cycle, each cycle consists of two meetings. Each cycle has four stages, namely the planning stage, the implementation stage, the observation stage, and the reflection stage. Data collection techniques and procedures are observation, tests and documentation. This Classroom Action Reasearch (CAR) was carried out in Makassar City with the research subjects being teachers and students totaling 18 people consisting of 13 male atudents and 5 female students. The data analysis technique in this research is qualitative and quantitative (mixed method) data analysis. The results showed that there was an increase in student learning outcomes in social studies subjects with the achievement of completeness of pre action learning outcomes in the less category, in the first cycle obtained 8 students complete with the achievement of mastery learning outcomes was in the sufficient category, while in the second cycle 15 students were obtained trough the achievement of complete learning in the good category. The conclusion in this study is that the application of the make a match type of cooperative learning model can improve student learning outcomes in social studies subjects for students in  Makassar City.